Euro area banks' interest rate risk exposure to level, slope and curvature swings in the yield curve. (6th June 2022) - Foos, Daniel; Lütkebohmert, Eva; Markovych, Mariia; Pliszka, Kamil
Abstract: We investigate the interest rate risk exposures of euro area banks during times of crises and very low interest rates. First, we assess sensitivities of banks' stock prices to changes in the level, slope and curvature of the yield curve using the Bayesian DCC M‐GARCH model. Our findings reveal that stock price sensitivities change over time and that, on average, banks benefit from increases in the level, slope and curvature of the yield curve. Second, we observe that banks with higher capital ratios, more customer lending and less deposit financing are particularly sensitive to interest rate movements.